2019
DOI: 10.1016/j.str.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Combining Transient Expression and Cryo-EM to Obtain High-Resolution Structures of Luteovirid Particles

Abstract: Highlights d Establish method for producing high-titer luteovirus VLPs in plants d Presents high-resolution cryo-EM structure of BYDV and PLRV VLPs d Provides platform for rational interrogation of luteovirid capsid formation d Coat protein models for the type-species in each of the three Luteoviridae genera

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Here, however, we observed that VLPs that expressed in plants have a heterogeneous structure and aggregation-prone particles ( Figure S4). A similar phenomenon was observer when PEMV1 CP was expressed in plants [30].…”
Section: Discussionsupporting
confidence: 71%
“…Here, however, we observed that VLPs that expressed in plants have a heterogeneous structure and aggregation-prone particles ( Figure S4). A similar phenomenon was observer when PEMV1 CP was expressed in plants [30].…”
Section: Discussionsupporting
confidence: 71%
“…However, in vitro assembly is only feasible on a small scale with a virus, such as TMV, that has been extensively studied. While expression of the coat protein (CP) and self-assembly into VLPs has been very effective with isometric plant viruses [ 5 , 9 , 10 , 11 , 12 ], expression of the coat protein alone in the case of helical viruses generally results in either low yields, very heterogeneous material, or both. For example, the non-replicating pEAQ- HT system [ 13 ] has been used for the production of turnip mosaic virus VLPs by expression of coat protein alone [ 14 ], and tobacco mosaic virus VLPs by co-expression of coat protein with RNA bearing a TMV origin of assembly (OAS; [ 15 ]); however only relatively low yields were reported.…”
Section: Introductionmentioning
confidence: 99%
“…The particles of the obtained chimeric virus may be a fascinating object of study under cryo-electron microscopy [49] taking into consideration that the structure of the ryegrass mottle virus (RMV) capsid was resolved at 2.9 angstroms [50] and that most non-enveloped icosahedral viruses have the same type of icosahedral capsids.…”
Section: Discussionmentioning
confidence: 99%